Diaphragm and preparation method thereof, battery and electric device
The separator prepared by cross-linking reaction using trapezoidal polymer and cross-linking agent is solved, and the separator capacity retention rate in lithium-ion batteries is improved, the rate performance and mechanical properties of the battery are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202311356622.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The commonly used polyolefin separators in lithium-ion batteries have a large capacity attenuation after running for multiple turns and have low capacity retention.
The separator is prepared by crosslinking reactants from trapezoidal polymer and crosslinking agent. The trapezoidal polymer is bridged with dioxane. The crosslinking agent has at least two hydroxymethyl groups, and a separator with high mechanical properties is formed by crosslinking reaction.
Effectively improve the rate performance and mechanical properties of lithium-ion batteries, so that they can maintain excellent mechanical performance and porosity after long-term cycles, reduce the capacity attenuation rate after multiple turns of the battery, improve the capacity retention rate, and extend the battery life.
Smart Images

Figure CN119864596A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to a diaphragm and a method for preparing the same, a battery, and an electrical device. Background Art
[0002] The separator plays an important role in lithium-ion batteries, such as conducting ions, isolating the positive and negative electrodes of the battery, and preventing short circuits. The commonly used lithium-ion battery separator is a porous separator made of polyolefins. When used in batteries, there are problems such as large capacity attenuation and low capacity retention after multiple cycles. Summary of the invention
[0003] In view of the above problems, the present application proposes a diaphragm and a method for preparing the same, a battery and an electrical device, which can improve the technical problem of low battery capacity retention rate.
[0004] In a first aspect, an embodiment of the present application provides a diaphragm, the diaphragm comprising a reactant obtained by cross-linking a ladder polymer and a cross-linking agent, wherein the ladder polymer is a ladder polymer with dioxane as a bridge.
[0005] In the technical solution of the embodiment of the present application, on the one hand, various rigid and twisted structures in the ladder polymer molecules are utilized to cause the polymer to produce a large number of microporous structures when forming a dense stack. When it is cross-linked with the cross-linking agent, it can still meet the porosity requirements of the diaphragm, effectively improving the rate performance of the lithium-ion battery. On the other hand, the cross-linked structure formed by the ladder polymer and the cross-linking agent is utilized to improve the mechanical properties of the diaphragm, so that it can still maintain excellent mechanical properties and porosity after long-term cycling, effectively reducing the capacity attenuation rate of the battery after multiple cycles of operation, improving the capacity retention rate, and extending the battery life.
[0006] In some embodiments, the ladder polymer has a benzene ring, the cross-linking agent has at least two hydroxymethyl groups, and the reactant comprises a cross-link formed by the reaction of the hydroxymethyl groups with the hydrogen on the benzene ring.
[0007] When the reactants contain cross-linked bonds formed by the reaction of hydroxymethyl groups with hydrogen on benzene rings, the diaphragm can exist in the electrolyte for a long time, and it has both good porosity and mechanical properties, and the mechanical properties decay little during battery operation, thereby improving the battery capacity retention rate and extending the battery life.
[0008] Optionally, the cross-linking agent has two hydroxymethyl groups.
[0009] In some embodiments, the reactants include:
[0010]
[0011] In some embodiments, the porosity of the membrane is greater than or equal to 43.5%, and can be optionally 43.5%-69.5%.
[0012] When the porosity is within the above range, the diaphragm has both better ion conductivity and excellent mechanical properties, which is beneficial to improving the capacity retention rate.
[0013] In some embodiments, when the thickness of the separator is 7 μm, the longitudinal tensile strength of the separator is
[0014] ≥1467kgf / cm 2 , transverse tensile strength ≥857kgf / cm 2 .
[0015] The above-mentioned diaphragm has excellent longitudinal tensile strength and transverse tensile strength, good mechanical properties, and is beneficial to improving the capacity retention rate of the battery.
[0016] In some embodiments, the crosslinking agent is a bis(hydroxymethyl) crosslinking agent, and the crosslinking degree of the reactants is 5%-20%.
[0017] In the second aspect, the present application provides a method for preparing the diaphragm in the above-mentioned embodiment, which comprises: dissolving the ladder polymer, the cross-linking agent and the acidic catalyst in an organic solvent to obtain a casting liquid; applying the casting liquid to form a coating, allowing the organic solvent to evaporate to form a film, and then heat treating at 100-120°C.
[0018] The preparation method provided in the present application is controllable in operation and can be industrially produced. It can form a film without stretching, and the prepared diaphragm can remain insoluble in the electrolyte for a long time and has sufficient mechanical properties, which can improve the battery rate performance and improve the capacity retention rate.
[0019] In some embodiments, the ladder polymer includes at least one of polymers ag:
[0020]
[0021] In the above polymer ag, R1 is selected from any one of hydrogen, halogen, and methyl; R2 is selected from any one of hydrogen, methyl, ethyl, and trifluoromethyl; R4 is selected from any one of hydrogen, halogen, methyl, ethyl, propyl, isopropyl, butyl, aromatic group, and trifluoromethyl.
[0022] Optionally, the ladder polymer is polymer a, and further optionally, R1 in polymer a is hydrogen.
[0023] In some embodiments, the crosslinking agent includes a bis(hydroxymethyl) crosslinking agent, which may be at least one of 2,6-bis(hydroxymethyl)-4-methylphenol, 4,4'-dihydroxymethylbiphenyl, and 4,4'-dihydroxydiphenylmethane.
[0024] In some embodiments, the amount of cross-linking agent added is 2.5%-10% by weight of the ladder polymer, and optionally 5%-10%.
[0025] In some embodiments, the acidic catalyst comprises methanesulfonic acid.
[0026] In some embodiments, the ratio of the added amount of the ladder polymer to the acid catalyst is 100 g: 0.01-0.05 ml.
[0027] By adding the amount within the above range, it is beneficial to obtain a reasonable reaction rate, improve the preparation efficiency and the quality of the diaphragm.
[0028] In some embodiments, the heat treatment time is greater than or equal to 6 hours, and can be optionally 12-18 hours.
[0029] Within the above time range, the prepared diaphragm has a better capacity retention rate.
[0030] In a third aspect, the present application provides a battery, which includes the battery cell in the above embodiment.
[0031] In a fourth aspect, the present application provides an electrical device, which includes the battery in the above embodiment, and the battery is used to provide electrical energy.
[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. In addition, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0034] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;
[0035] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;
[0036] Figure 3 A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;
[0037] Figure 4 This is a schematic diagram of the structure of the electrode assembly of some embodiments of the present application.
[0038] The accompanying drawings in the specific implementation manner are as follows:
[0039] 1000-Vehicles;
[0040] 100-battery; 200-controller; 300-motor;
[0041] 10-box; 11-first part; 12-second part;
[0042] 20 - battery cell; 21 - end cap; 21a - electrode terminal; 22 - housing; 23 - electrode assembly; 231 - positive electrode sheet; 233 - negative electrode sheet; 235 - separator. DETAILED DESCRIPTION
[0043] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0045] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0046] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0047] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0048] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0049] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0050] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0051] At present, the separator plays an important role in lithium-ion batteries, such as conducting ions, isolating the positive and negative electrodes of the battery, and preventing the battery from short circuiting. The commonly used lithium-ion battery separator is a porous separator made of polyolefins. Polyolefin separators have disadvantages such as low porosity and poor wettability with electrolytes. When used in batteries, they have problems such as low battery rate performance, large capacity attenuation after multiple cycles of operation, and low capacity retention.
[0052] In order to improve the above problems, the present application attempts to use ladder polymers to replace polyolefins to make diaphragms.
[0053] In the present application, a ladder polymer refers to a ladder polymer with dioxane as a bridge, for example, dioxane is obtained by condensation reaction of monomers containing o-hydroxyphenol and 2,3,5,6-tetrafluoroterephthalonitrile, wherein the monomers containing o-hydroxyphenol also include at least one of spiroindole, spiroindole, diethyleneanthracene, triptycene, terephthalate, tetraphenylethylene and the like, these units can greatly affect the stacking of polymer chains, resulting in the inability of the polymer to be effectively stacked when forming a dense stack, thereby generating a large number of micropores.
[0054] Therefore, the ladder polymer has a free volume element with a persistent shape, which can be penetrated by small molecules and ions. When it is applied to a diaphragm, it can effectively improve the wettability of the diaphragm due to its large amount of microporous structure.
[0055] However, in actual operation, it was found that although the porosity of the diaphragm was significantly improved compared with polyolefin, the capacity decay in the battery increased after multiple cycles of operation, and the problem of large capacity decay and low capacity retention after multiple cycles of operation could not be solved. Research has found that the main reason for the above problems is that although the initial mechanical properties of the diaphragm made by direct film formation of the ladder polymer are similar to those of the polyolefin diaphragm, its mechanical properties are significantly decayed after the battery has been operated for multiple cycles, resulting in a significant decay in the battery capacity.
[0056] In view of this, in order to improve the technical problem of low battery capacity retention rate, the present application designs a diaphragm, which includes a reactant cross-linked by a ladder polymer and a cross-linking agent, wherein the ladder polymer refers to a ladder polymer bridged by dioxane. In the technical scheme of the embodiment of the present application, on the one hand, various rigid and twisted structures in the ladder polymer molecules are used to cause the polymer to produce a large number of microporous structures when forming a dense stack. The reactant obtained after the ladder polymer and the cross-linking agent are cross-linked can still meet the diaphragm porosity requirements and effectively improve the rate performance of the lithium-ion battery. On the other hand, the cross-linked structure generated after the ladder polymer and the cross-linking agent are cross-linked is used to improve the mechanical properties of the diaphragm, so that it can still maintain excellent mechanical properties and porosity after long-term circulation, effectively reducing the capacity attenuation rate after the battery runs for multiple cycles, improving the capacity retention rate, and extending the battery life.
[0057] The battery disclosed in the embodiment of the present application can be used in, but not limited to, electric devices such as vehicles, ships or aircraft. A power supply system comprising the battery cells and batteries disclosed in the present application can be used to form the electric device, which is helpful to alleviate the problem of low battery rate performance and low capacity retention rate, and improve the battery rate performance and battery life.
[0058] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0059] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0060] Please refer to Figure 1, Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0061] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0062] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may also include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0063] Please refer to Figure 2 , Figure 2 An exploded view of a battery 100 provided in some embodiments of the present application. The battery 100 includes a housing 10 and a battery cell 20, and the battery cell 20 is contained in the housing 10. The housing 10 is used to provide a storage space for the battery cell 20, and the housing 10 can adopt a variety of structures. In some embodiments, the housing 10 can include a first part 11 and a second part 12, and the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 can be a hollow structure with one end open, and the first part 11 can be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the housing 10 formed by the first part 11 and the second part 12 can be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0064] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.
[0065] Each battery cell 20 may be a secondary battery or a primary battery. The battery cell 20 may be cylindrical, flat, rectangular or in other shapes.
[0066] Please refer to Figure 3 , Figure 3 The schematic diagram of the exploded structure of the battery cell 20 provided in some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.
[0067] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0068] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0069] The electrode assembly 23 is a component where an electrochemical reaction occurs in the battery cell 20. One or more electrode assemblies 23 may be contained in the housing 22.
[0070] See also Figure 4 The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet 233, and a separator 235 located between the positive electrode sheet 231 and the negative electrode sheet 233, which are wound or stacked together.
[0071] The parts of the positive electrode sheet 231 and the negative electrode sheet 233 with active materials constitute the main body of the electrode assembly 23, and the parts of the positive electrode sheet 231 and the negative electrode sheet 233 without active materials each constitute a tab. The positive tab and the negative tab can be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab is connected to the electrode terminal 21a to form a current loop.
[0072] According to some embodiments of the present application, the diaphragm includes a reactant obtained by cross-linking a ladder polymer and a cross-linking agent, wherein the ladder polymer refers to a ladder polymer with dioxane as a bridge.
[0073] Cross-linking refers to the process of using a cross-linking agent to connect the molecular chains of multiple ladder polymers with covalent bonds to form a network or bulk polymer.
[0074] It should be noted that the diaphragm can be a single-layer porous film formed by the reactants of a ladder polymer and a cross-linking agent, or it can be a multi-layer composite film. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, but at least one layer is a porous film formed by the reactants of a ladder polymer and a cross-linking agent. In addition, in some optional examples, a coating layer can be provided on at least one side of the diaphragm, and the coating layer can be, for example, a ceramic coating, a metal oxide coating, etc.
[0075] In the technical solution of the embodiment of the present application, on the one hand, various rigid and twisted structures in the ladder polymer molecules are utilized to cause the polymer to produce a large number of microporous structures when forming a dense stack. The reactants obtained after cross-linking the ladder polymer and the cross-linking agent can still meet the porosity requirements of the diaphragm and effectively improve the rate performance of the lithium-ion battery. On the other hand, the cross-linked structure generated after cross-linking the ladder polymer and the cross-linking agent is utilized to improve the mechanical properties of the diaphragm, so that it can still maintain excellent mechanical properties and porosity after long-term cycling, effectively reducing the capacity attenuation rate of the battery after multiple cycles of operation, improving the capacity retention rate, and extending the battery life.
[0076] In some embodiments, the ladder polymer has a benzene ring, the cross-linking agent has at least two hydroxymethyl groups, and the reactant comprises a cross-link formed by the reaction of the hydroxymethyl groups with the hydrogen on the benzene ring.
[0077] The cross-linking bonds formed by the reaction of hydroxymethyl groups with hydrogen on the benzene ring effectively enhance the mechanical properties of the diaphragm and enable it to exist in the electrolyte for a long time. Although the porosity is lower than that of the uncross-linked ladder polymer, it is still better than traditional polyolefins and can improve wettability.
[0078] The above-mentioned diaphragm prepared by the reactants of cross-linking the ladder polymer and the cross-linking agent having hydroxymethyl can exist in the electrolyte for a long time, has good porosity and good mechanical properties. The mechanical properties decay little during the operation of the battery and have good stability, thereby improving the battery capacity retention rate and extending the battery life.
[0079] Optionally, the cross-linking agent has two hydroxymethyl groups.
[0080] That is, the crosslinking agent is a bishydroxymethyl crosslinking agent, which refers to a class of compounds having bishydroxymethyl groups that can undergo crosslinking reactions with the ladder polymer. That is, the reactant is the crosslinked product of the ladder polymer and the bishydroxymethyl crosslinking agent.
[0081] Optionally, the bis(hydroxymethyl) crosslinking agent includes at least one of 2,6-bis(hydroxymethyl)-4-methylphenol, 4,4'-dihydroxymethylbiphenyl, and 4,4'-dihydroxydiphenylmethane, and may be 2,6-bis(hydroxymethyl)-4-methylphenol.
[0082] In some embodiments, the reactants include:
[0083]
[0084] Wherein, n represents the degree of polymerization, which can be selected according to actual needs and is not limited here.
[0085] In some embodiments, the membrane has a porosity of 43.5% or greater.
[0086] When the porosity is within the above range, the diaphragm has both better ion conductivity and excellent mechanical properties, which is beneficial to improving the capacity retention rate.
[0087] Illustratively, the porosity of the separator is any one of 43.5%, 45%, 50%, 55%, 60%, 65%, 69.5%, 70%, or between any two values.
[0088] Optionally, the membrane has a porosity of 43.5%-69.5%.
[0089] In some embodiments, when the thickness of the separator is 7 μm, the longitudinal tensile strength of the separator is
[0090] ≥1467kgf / cm 2 , transverse tensile strength ≥857kgf / cm 2 .
[0091] It can be understood that the above-mentioned longitudinal tensile strength and transverse tensile strength both refer to the initial tensile strength of the diaphragm.
[0092] The above-mentioned diaphragm has excellent longitudinal tensile strength and transverse tensile strength, good mechanical properties, and is beneficial to improving the capacity retention rate of the battery.
[0093] In some embodiments, the crosslinking agent is a bis(hydroxymethyl) crosslinking agent, and the crosslinking degree of the reactants is 5%-20%.
[0094] Since the cross-linking agent is a bis(hydroxymethyl) cross-linking agent, the cross-linking degree of the above reactants = 2*the mass of the cross-linking agent / the mass of the ladder polymer.
[0095] Within the above cross-linking degree range, the separator has both good porosity and mechanical strength, which is beneficial to improving the rate performance and capacity retention rate of the battery.
[0096] According to some embodiments of the present application, the present application also provides a method for preparing the above-mentioned diaphragm, which comprises: dissolving a ladder polymer, a cross-linking agent and an acidic catalyst in an organic solvent to obtain a casting solution. Applying the casting solution to form a coating, volatilizing the organic solvent to form a film, and then heat treating at 100-120°C.
[0097] The process of coating the casting solution to form a coating layer includes, but is not limited to, coating the coating layer on a substrate having a smooth surface. For subsequent easy peeling, the substrate includes, but is not limited to, glass and the like.
[0098] Allowing the organic solvent to volatilize to form a film means that the organic solvent can volatilize to form a film layer under normal pressure and room temperature conditions, wherein the volatilization film-forming time can be selected according to the selection of a specific organic solvent. For example, the volatilization film-forming time is 10-24 hours.
[0099] The organic solvent is an organic solvent that can dissolve the ladder polymer, the crosslinking agent, and the acidic catalyst, has a low boiling point, and is easily volatile at room temperature. Optionally, the boiling point of the organic solvent is lower than 100°C, and it dissolves at a temperature far lower than the melting point of the ladder polymer, which can reduce energy consumption and make it easier for production equipment to meet requirements; further optionally, the organic solvent includes but is not limited to chloroform, tetrahydrofuran, dichloroethane or cyclohexane.
[0100] By first volatilizing to form a film and then heat treating at 100-120°C, the ladder polymer and the cross-linking agent in the membrane layer undergo a cross-linking reaction under the catalytic action of an acidic catalyst, and then peeling can be performed. The final diaphragm has uniform quality and thickness, good diaphragm quality, and is conducive to fully volatilizing the organic solvent and removing the acidic catalyst during the heat treatment process, thereby simplifying the preparation process.
[0101] The preparation method provided in the present application is controllable in operation and can be industrially produced. It can form a film without stretching, and the prepared diaphragm can remain insoluble in the electrolyte for a long time and has sufficient mechanical properties, which can improve the battery rate performance and improve the capacity retention rate.
[0102] According to some embodiments of the present application, the ladder polymer includes at least one of polymers ag:
[0103]
[0104] In the above polymer ag, R1 is selected from any one of hydrogen, halogen, and methyl; R2 is selected from any one of hydrogen, methyl, ethyl, and trifluoromethyl; R4 is selected from any one of hydrogen, halogen, methyl, ethyl, propyl, isopropyl, butyl, aromatic group, and trifluoromethyl.
[0105] Optionally, the ladder polymer is polymer a, and further optionally, R1 in polymer a is hydrogen.
[0106] The ladder polymer has a solvation cage that can enhance lithium ion transport, inhibit lithium dendrite formation, and reduce battery polarization and deposition / stripping overpotential during battery cycling, which is beneficial to improving the battery cycle life.
[0107] According to some embodiments of the present application, the cross-linking agent includes a bis(hydroxymethyl) cross-linking agent.
[0108] The bis(hydroxymethyl) crosslinking agent refers to a class of compounds having bis(hydroxymethyl) groups capable of undergoing crosslinking reactions with the ladder polymer. The bis(hydroxymethyl) crosslinking agent includes but is not limited to 2,6-bis(hydroxymethyl)-4-methylphenol, 4,4'-dihydroxymethylbiphenyl, and 4,4'-dihydroxydiphenylmethane.
[0109] Optionally, the cross-linking agent is 2,6-bis(hydroxymethyl)-4-methylphenol.
[0110] According to some embodiments of the present application, the added amount of the cross-linking agent is 2.5%-10% of the mass of the ladder polymer.
[0111] Illustratively, the amount of crosslinker added is any value among 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% of the mass of the ladder polymer or between any two values.
[0112] Optionally, the amount of the cross-linking agent added is 5%-10% of the mass of the ladder polymer.
[0113] Since the reactants are actually obtained by condensation reaction of ladder polymer and cross-linking agent, the acidic catalyst that can be used can be selected from known inorganic acids and organic acids, including but not limited to: mineral acids such as hydrochloric acid, sulfuric acid or phosphoric acid; organic acids such as oxalic acid, citric acid, formic acid, p-toluenesulfonic acid, methanesulfonic acid, trifluoroacetic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, naphthalenesulfonic acid or naphthalene disulfonic acid; Lewis acids such as zinc chloride, aluminum chloride, ferric chloride or boron trifluoride; and solid acids such as silicotungstic acid, phosphotungstic acid, silicomolybdic acid and phosphomolybdic acid.
[0114] According to some embodiments of the present application, the acidic catalyst includes methanesulfonic acid.
[0115] According to some embodiments of the present application, the ratio of the added amount of the ladder polymer to the acid catalyst is 100 g: 0.01-0.05 ml.
[0116] By adding the amount within the above range, it is beneficial to obtain a reasonable reaction rate and improve the preparation efficiency.
[0117] Illustratively, the ratio of the amount of the ladder polymer to the amount of the acid catalyst added is any one of 100 g:0.01 ml, 100 g:0.02 ml, 100 g:0.03 ml, 100 g:0.05 ml, or between any two values.
[0118] According to some embodiments of the present application, the heat treatment time is greater than or equal to 6 hours.
[0119] Within the above time range, the prepared diaphragm has a better capacity retention rate.
[0120] Exemplarily, the heat treatment time is any value among 6 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or between any two values.
[0121] Optionally, the heat treatment time is 12-18 hours.
[0122] According to some embodiments of the present application, the present application also provides a battery, comprising the separator of any of the above schemes.
[0123] According to some embodiments of the present application, the present application also provides an electrical device, comprising a battery according to any of the above schemes, and the battery is used to provide electrical energy to the electrical device.
[0124] The power-consuming device may be any of the aforementioned devices or systems using batteries.
[0125] According to some embodiments of the present application, the present application provides a diaphragm, the diaphragm includes a reactant cross-linked by a ladder polymer and a cross-linking agent, the ladder polymer is a ladder polymer bridged by dioxane, and the structural formula of the reactant is:
[0126]
[0127] Some specific embodiments are listed below to better illustrate the present application.
[0128] Example 1
[0129] Ladder polymers are prepared by the following steps:
[0130] Add 2,3,5,6-tetrafluoroterephthalonitrile and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindene in a 1:1 molar ratio to a three-necked flask containing 120 mL of DMF, and stir at room temperature for 20 minutes under N2 protection until the monomer is completely dissolved. Install a thermometer, adapter, and magnet in the three-necked flask and place it in a 50°C oil bath for 23 hours. After cooling to room temperature, pour the reactant into 500 ml of distilled water to precipitate the polymer, and filter to obtain the polymer. Then wash the product with methanol, DMF, and distilled water in turn and place it in an oven for drying.
[0131] The structural formula of the obtained ladder polymer (abbreviated as PIM) is as follows:
[0132]
[0133] The diaphragm is prepared by the following steps:
[0134] Take 10g of the above PIM and dissolve it in dichloroethane. At the same time, add 0.5g of 2,6-bis(hydroxymethyl)4-methylphenol and 2 drops of methanesulfonic acid. After stirring for 5 minutes, pour the obtained casting solution onto a glass plate. After slowly evaporating at room temperature for 1 day to form a film, place it in an oven at 110°C to react for 12 hours to obtain a diaphragm with a film thickness of 7μm.
[0135] Among them, the diaphragm obtained after preparation can be cut and sampled to obtain the initial weight M1, and then immersed in dichloroethane. The membrane is taken out after 24 hours, and the weight after drying is recorded as M2. When M1-M2≤5%M1, it is considered that the weight has no obvious change, indicating that the cross-linking is successful and a cross-linked structure is formed.
[0136] Cut a 2cm*2cm diaphragm to obtain an initial weight of 0.103g, soak it in 50ml of dichloroethane, take out the membrane after 24h, and the weight after drying is recorded as 0.100g. There is no obvious change in weight, indicating that the cross-linking is successful.
[0137] Examples 2-10 and Comparative Examples 1-2
[0138] The differences between the above embodiments and comparative examples and embodiment 1 are shown in Table 1.
[0139] The structural formula of the ladder polymer used in Examples 2-9 is shown in Example 1, and the structural formula of the ladder polymer used in Example 10 is as follows:
[0140]
[0141] Comparative Example 1 is a PE diaphragm.
[0142] The difference between Comparative Example 2 and Example 1 is that the dichloroethane solution of the ladder polymer is directly used as the casting solution, that is, the difference between Comparative Example 2 and Example 1 is that the ladder polymer does not contain a cross-linked structure.
[0143]
Determination of physical properties of diaphragm
[0144] The porosity, tensile strength, contact angle, and surface tension of the separators obtained in Examples 1-10 and Comparative Examples 1-2 were measured.
[0145] Porosity test method: The pore volume is obtained based on low temperature nitrogen adsorption.
[0146] Tensile strength test method: A tensile testing machine, a fixture and a dynamometer are required for testing. The material is fixed and connected to the tensile testing machine. The tensile testing machine can apply a constant load and record the elongation and stress of the material under different loads. The dynamometer can accurately measure the load on the material.
[0147] Contact angle test method: The contact angle of the sample is measured by an optical contact angle meter. The sample is immersed in the liquid, and then the sample is pulled up to form a meniscus on both sides of the sample. The angle formed by the meniscus and the liquid plane is the contact angle.
[0148] Surface tension test method: Surface tension can be measured using a surface tension tester. When the probe interacts with the sample surface, the force measured by the balance can be used to calculate the surface tension.
[0149] The measurement results are shown in Table 2.
[0150]
Battery performance
[0151] 1. Preparation of positive electrode sheet
[0152] NCM811, conductive carbon black and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 97:1:2 and stirred until the system was uniform. The mixture was coated on aluminum foil, dried, cold pressed and cut to obtain a positive electrode sheet.
[0153] 2. Preparation of negative electrode sheet
[0154] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed with deionized water in a mass ratio of 96:2:2, and stirred evenly to obtain negative electrode slurry. The negative electrode slurry was coated on copper foil, dried, cold pressed, cut into pieces, and welded to the pole ears to obtain the negative electrode sheet.
[0155] 3. Preparation of electrolyte
[0156] In a dry argon environment, diethyl carbonate, ethylene carbonate and propylene carbonate (weight ratio of 1:1:1) are mixed, and LiPF6 is added and mixed evenly to form a basic electrolyte, in which the concentration of LiPF6 is 1.15 mol / L.
[0157] 4. Preparation of lithium-ion batteries
[0158] The obtained positive electrode sheet, the separator and the negative electrode sheet prepared in each embodiment and comparative example are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.
[0159] 1C rate test method: 1 / 3C charge, 1 / 3C discharge (capacity recorded as C1), 1 / 3C charge, 1C discharge (capacity recorded as C2), with a 1 minute interval after each charge and discharge. The 1C rate in Table 2 is C1 / C2.
[0160] The 1C / 1C capacity retention rate test method is: 1C charge and 1C discharge are continuously charged and discharged for 500 cycles, with a 1 minute interval after each charge and discharge, to obtain the capacity retention rate of the 500th cycle, recorded as 1C / 1C capacity retention rate 500cycle.
[0161] The test results of various embodiments and comparative examples are shown in Table 2.
[0162] Table 1 Differentiating parameters of each embodiment and comparative example
[0163]
[0164] Table 2 Test results
[0165]
[0166]
[0167] According to the embodiments and comparative examples, the diaphragm provided in the present application, which is made of the reactant of a ladder polymer and a cross-linking agent after cross-linking, has excellent porosity and excellent mechanical properties, and the battery using the diaphragm has excellent rate performance and excellent capacity retention.
[0168] According to Example 1 and Comparative Examples 1-2, the porosity and initial tensile strength of the diaphragm directly prepared with the ladder polymer are improved compared with the PE film, but the tensile strength decay after 500 cycles is greater than that of Comparative Example 1, resulting in the capacity retention rate of the battery using it after 500 cycles being lower than that of Comparative Example 1. The diaphragm made of the reactants of the ladder polymer and the cross-linking agent in Example 1, although the porosity is lower than that of Comparative Example 2, it is still higher than that of Comparative Example 1. The initial tensile strength of Example 1 is significantly improved compared with Comparative Examples 1-2, and the tensile strength decay after 500 cycles is small, thereby improving the capacity retention rate of the battery using it after 500 cycles.
[0169] According to Examples 1-4, the amount of cross-linking agent added affects the final diaphragm performance, wherein when the amount of the cross-linking agent added is 2.5%-10% of the mass of the ladder polymer, the battery using it has a better capacity retention rate, and when the amount of the cross-linking agent added is 5%-10% of the mass of the ladder polymer, the mechanical properties of the diaphragm and the capacity retention rate of the battery using it are better.
[0170] According to Examples 1 and 5, when the ratio of the amount of the ladder polymer to the amount of the acid catalyst added is 100 g: 0.01-0.05 ml, the diaphragm has better mechanical properties and capacity retention.
[0171] According to Examples 1, 6-7, the drying temperature affects the performance of the diaphragm. When the drying temperature is 100-120°C, the diaphragm has better mechanical properties and capacity retention rate.
[0172] According to Examples 1, 8-9, it can be seen that the drying time affects the performance of the diaphragm. When the drying time is 6h-18h, the diaphragm has better mechanical properties, and the battery using the diaphragm has a higher capacity retention rate.
[0173] According to Examples 1 and 10, although the specific composition of the ladder polymer has changed, it is still possible to use a cross-linking agent to cross-link the separator to improve the mechanical properties of the separator and the capacity retention rate of the battery using the separator.
[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application is described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A diaphragm, characterized in that: The separator includes a reactant obtained by cross-linking a ladder polymer and a cross-linking agent, wherein the ladder polymer is a ladder polymer using dioxane as a bridge.
2. The diaphragm according to claim 1, characterized in that The ladder polymer has a benzene ring, the cross-linking agent has at least two hydroxymethyl groups, and the reactant comprises a cross-linking bond formed by the reaction of the hydroxymethyl groups with hydrogen on the benzene ring; Optionally, the cross-linking agent has two hydroxymethyl groups.
3. The diaphragm according to claim 1, characterized in that The reactants include:
4. The diaphragm according to any one of claims 1 to 3, characterized in that: The porosity of the diaphragm is greater than or equal to 43.5%, and can be optionally 43.5%-69.5%.
5. The diaphragm according to any one of claims 1 to 3, characterized in that: When the thickness of the diaphragm is 7 μm, the longitudinal tensile strength of the diaphragm is ≥ 1467 kgf / cm 2 , transverse tensile strength ≥857kgf / cm 2 .
6. The diaphragm according to any one of claims 1 to 3, characterized in that: The crosslinking agent is a dimethylol crosslinking agent, and the crosslinking degree of the reactant is 5%-20%.
7. The method for preparing a diaphragm according to any one of claims 1 to 6, characterized in that: include: dissolving the ladder polymer, the cross-linking agent and the acidic catalyst in an organic solvent to obtain a casting solution; The casting solution is applied to a casting substrate, the organic solvent is volatilized to form a film, and then heat-treated at 100-120°C.
8. The preparation method according to claim 7, characterized in that: The ladder polymer comprises at least one of polymers ag: In the above polymer ag, R1 is selected from any one of hydrogen, halogen, and methyl; R2 is selected from any one of hydrogen, methyl, ethyl, and trifluoromethyl; R4 is selected from any one of hydrogen, halogen, methyl, ethyl, propyl, isopropyl, butyl, aromatic group, and trifluoromethyl; Optionally, the ladder polymer is polymer a, and further optionally, R1 in the polymer a is hydrogen.
9. The preparation method according to claim 7, characterized in that: The crosslinking agent includes a bis(hydroxymethyl) crosslinking agent, which can be selected from at least one of 2,6-bis(hydroxymethyl)-4-methylphenol, 4,4'-dihydroxymethylbiphenyl, and 4,4'-dihydroxydiphenylmethane.
10. The preparation method according to claim 7, characterized in that: The added amount of the cross-linking agent is 2.5%-10% of the mass of the ladder polymer, and can be optionally 5%-10%.
11. The preparation method according to claim 7, characterized in that: The acidic catalyst includes methanesulfonic acid.
12. The preparation method according to claim 7, characterized in that: The ratio of the added amount of the ladder polymer to the added amount of the acid catalyst is 100g:0.01-0.05ml.
13. The preparation method according to claim 7, characterized in that: The heat treatment time is greater than or equal to 6 hours, and can be optionally 12-18 hours.
14. A battery, characterized in that: It comprises the diaphragm according to any one of claims 1 to 6.
15. An electrical device, characterized in that: It comprises the battery according to claim 14, wherein the battery is used to provide electrical energy.